THE EFFECT OF READING HABIT ON EFL LEARNERS’ VOCABULARY SIZE - Muhamad Suhaili (Sinar Lima, 2024)
There were 128 students in sixth semester, the researcher found some difficulties that faced by students, such as a lack of vocabulary numbers, which causes poor understanding in reading. Besides, the students do not want to read an English text since they feel difficult to understand the meaning of the text. The purpose of this research was to investigate the effect of reading habits on EFL learners’ vocabulary size. This research employs a quantitative approach with ex post facto design. The participants of this research were 69 third-year students in English Language Education Study Program at Islamic State University of Mataram. Data of students’ vocabulary size were garnered through Lemma-based Vocabulary Size Test (LVST), while their reading habits were elicited through self-report measurement scale. The gained data then were analyzed using one-way ANOVA and post-hoc analysis to compare students’ vocabulary size based on high, medium, and low reading habit. The results of this research were 1) There is a significant difference in students' vocabulary size based on their reading habits (high, medium, and low) indicated by p-value Sig. 0.004 <0.005. Nevertheless, the post-hoc analysis showed that high vs low and high vs medium reading habit categories differ significantly. 2) Reading habit has minor effect size on EFL learners’ vocabulary size as indicated by Cohen’s d value .283. Therefore, despite significant differences between high vs low and high vs medium category, reading habit is shown to have small effect on students’ vocabulary size.